Theoretical and experimental study of the economic behavior irrational component of ukrainian society in specific markets - Khovrat, A.; Teslenko, D.; Huliiev, N.; Kyriy, V. (ХНУРЕ, 2023)
The subject matter of the article is the theoretical-methodical and applied principles of behavioural economics and their implementation in Ukrainian society. The goal of the work is to analyse the theory of irrationality in the economic context to find out what its character is in modern Ukrainian conditions, as well as to confirm the main paradoxes inherent in the individual’s decision-making behaviour. The following tasks were solved in the article: highlighting important aspects of the theory of irrationality for experimental analysis; determination of the methodology of experiments based on internationally recognized works; proposing a hypothesis regarding Ukrainian realities; conducting experiments according to the proposed methodology to test the proposed hypotheses and systematize the obtained results. The following methods are used: analytical and inductive methods for determining the set of behavioural experiments and building hypotheses regarding their results; experimental method and method of mathematical processing to check the presence of selected behavioural deviations in Ukraine. The following results were obtained: it was determined that in Ukrainian society there is a difference between the degree of individualistic attitudes in different age groups; determined change in the perception of information of different generations as a result of more significant digitization of the young population; a higher tendency of children to risk for certain conditions is determined; the similarity of the obtained results of the experiments with the global ones are established and the impact of technologies on the economic behaviour of individuals and the peculiarities caused by the historical context and expanded access to information, in general, are determined. Conclusions: the use of analytical and inductive methods in combination with an experimental approach confirmed the existence of some of the classic behavioural patterns for modern Ukrainian society, in particular: the Allais paradox, the effect of bounded rationality, the effect of joining the majority, the effect of ownership and asymmetric dominance. In addition, based on the obtained results, it was determined that for Ukraine there is a significant difference between the nature of irrationality in different age groups, however, the postulation of this statement beyond the selected target groups requires additional research, as well as consideration of the context of other market entities.
Keywords: behaviour; irrationality; ukrainian society; decision-making process